Identité sexuelle/sexuée/de sexe? Trois modes de conceptualisation du rapport entre sexe et genre - Mathieu, Nicole-Claude (Catégorisation de sexe et constructions scientifiques, 1989)
Keywords: approches et analyses; corps; cours; discipline; discours dominant; essentialisation; féminisme matérialiste; genre; histoire et politique; identité sexuelle; identités; naturalisation; philosophie politique; premier cycle; sciences; sciences humaines; sex3383; sexe; sexe/genre; systèmes d'oppressions; thématiques; épistémologie; épistémologies féministes

Polity and Group Difference: A Critique of the Ideal of Universal Citizenship - Young, Iris Marion (Ethics, 1989)
Keywords: approches et analyses; cours; discipline; droits civiques; histoire et politique; intersectionnalité; justice sociale; philosophie politique; pol4212; premier cycle; science politique; science politique et droit; sciences humaines; thématiques

The sexual contract - Pateman, Carole (Standford University Press, 1988)
In this remarkably original work of political philosophy, one of today's foremost feminist theorist challenges the way contemporary society functions by questioning the standard interpretation of an idea that is deeply embedded in American and British political thought: that our rights and freedoms derive from the social contract explicated by Locke, Hobbes, and Rousseau and interpreted in the United States by the Founding Fathers.
Keywords: 1900-1999; 1980-1989; amériques; citoyenneté; contrat social; cours; discipline; droits des femmes*; fem1000; incontournable; philosophie politique; premier cycle; périodes historiques; régions géographiques; sciences humaines; thématiques; théories féministes; états-unis

Narcissism, femininity and alienation - Bartky, Sandra Lee (Social Theory and Practice, 1982)
Keywords: amériques; cours; discipline; fem1000; féminisme marxiste; philosophie politique; premier cycle; ressource en ligne; régions géographiques; sciences humaines; sexualité; thématiques; états-unis